Antimicrobial Activity of Some Marine Sponges from San Juan, Batangas - Raymundo, Asuncion K.; Zulaybar, T.O.; Corpuz, G.P. (1988)
The water ethanol and acetone extracts of twenty-nine samples from fifteen species of marine sponges obtained from China Sea Waters in San Juan, Batangas were assayed for antimicrobial activity. Using Bacillus subtilis, Escherichia coli, Staphylococcus aureus, Micrococcus luteus, Proteus vulgaris, Pseudomonas solanacearum and Candida utilis as test organisms, 11 of the 29 samples had ethanol-soluble, 9 water-soluble and 4 acetone-soluble components which inhibited the growth of one or more of the seven test organisms. Only 2 species, Phyllospongia sp., and Halichondria panicea showed antimicrobial activity in all the three types of extracts.
Includes bibliographical references (pages 195-197)
Keywords: Biological Sciences; Antimicrobial metabolites; Marine sponges, Porifera; San Juan, Batangas